Stampacchia variational inequality with weak convex mappings. (3rd October 2018) - Balaj, Mircea
ABSTRACT: In this paper, the concept of weak convex set-valued mapping is introduced and various conditions for a set-valued mapping to be weak convex are given. Then, existence theorems for the Stampacchia variational inequality problem are established, when the involved mapping is weak convex.